Qualitative Case Study of Governmental Communication and Media Strategy in Yemen’s Presidential Leadership Council - Osid Ahmed Abdullah Hageb; Dian Eka Rahmawati; Ajree Ducol Malawani (UNIVERSITAS MUHAMMADIYAH MATARAM, 2026)
This study examines how Yemen’s Presidential Leadership Council (PLC) employs governmental communication and media strategy to exercise authority in a conflict-affected, non-electoral governance context. Through a systematic qualitative analysis of official statements, media interviews, and diplomatic engagements conducted between April 2022 and December 2025, the study shows that the PLC relies fundamentally on communication as a performative mechanism of authority construction. In the absence of electoral mandates, the council continuously invokes procedural, performance-based, and normative legitimacy claims to justify its authority. However, this communicative authority remains inherently fragile. It is undermined by structural fragmentation that produces contradictory messaging and uneven circulation across a highly fragmented media landscape comprising more than 200 faction-aligned outlets, as well as predominantly crisis-driven, reactive communication patterns. The findings demonstrate that coordination failures stem not from technical or strategic deficiencies, but from the political structure itself. When authority is dispersed among multiple power centers backed by competing external patrons, unified communication becomes structurally impossible as a sustained and routinized practice. Under these conditions, crisis communication normalizes as the primary mode of governance, constraining the capacity of non-electoral authorities to project coherent legitimacy or articulate long-term governance visions.